2006
DOI: 10.1002/anie.200601351
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear Double‐Stranded Metallosupramolecular Ruthenium Complexes: Potential Anticancer Drugs

Abstract: Platinum metallodrugs are among the most effective clinical agents for the treatment of cancer, and three such agents (cisplatin, carboplatin, and oxaliplatin) are in widespread use. These agents are believed to act by binding to DNA and to have similar molecular-level actions.[1] Clinical problems include acquired cisplatin resistance the limited spectrum of cancers that can be treated. To address these issues, alternative metallodrug designs that are distinct from cisplatin and have different molecular-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 38 publications
1
62
0
1
Order By: Relevance
“…Related unsaturated dinuclear ruthenium double helicates, capable of classic coordinative binding to DNA, show greatly improved cytotoxicity towards the same cell lines (30-fold more active than cisplatin). These complexes illustrate the many possibilities of using metallosupramolecular architectures in anticancer drug design [35].…”
Section: Non-covalent Interactions With Dnamentioning
confidence: 91%
See 1 more Smart Citation
“…Related unsaturated dinuclear ruthenium double helicates, capable of classic coordinative binding to DNA, show greatly improved cytotoxicity towards the same cell lines (30-fold more active than cisplatin). These complexes illustrate the many possibilities of using metallosupramolecular architectures in anticancer drug design [35].…”
Section: Non-covalent Interactions With Dnamentioning
confidence: 91%
“…Related unsaturated dinuclear ruthenium double helicates, capable of classic coordinative binding to DNA, show greatly improved cytotoxicity towards the same cell lines (30-fold more active than cisplatin). These complexes illustrate the many possibilities of using metallosupramolecular architectures in anticancer drug design [35].These examples not only illustrate the role of noncovalent DNA interactions, but also the newly emerging trend of using the metal in a scaffold, rather than as the reactive centre. In a highly modular approach, the use of a metal centre as a building block allows for the spatial orientation of other functionalities (as part of the ligands), which in turn interact favourably with the target via, for instance, hydrogen bonds (phosphate clamps) or p-stacking interactions (helicates).…”
mentioning
confidence: 91%
“…Ruthenium complexes have shown important biological activity and are becoming increasingly important in both bioinorganic chemistry and anticancer chemotherapy. [1][2][3][4][5] The water solubility of ruthenium compounds has been greatly increased by using dialkyl sulfoxide derivatives such as in [trans-RuCl 4 …”
Section: Introductionmentioning
confidence: 99%
“…[33] The flexible 23 and 24 (Scheme 10) were designed to induce DNA binding modes analogous to other metallosupramolecular cylinders developed by the same group. [34] Although it was not possible to obtain the absolute IC 50 value for these complexes for solubility reasons, it was observed that 23 and 24 would have an IC 50 of approximately 80-100 μm for HBL100 cells. No significant difference in cytotoxicity is present between the mixture and the enantiopure complexes.…”
Section: Dinuclear Polypyridyl Metal Complexesmentioning
confidence: 97%